Informed Consent in Medical Practice: A Reconstruction of the Concept of Consent to Medical Procedures from Legal and Bioethical Perspectives - Desy Kartika Ningsih; Yudhi Hertanto; Anna Veronica Pont; Silvester Magnus Loogman Palit; Tumian Lian Daya Purba (Dinasti Research, 2026)
The reform of Indonesia’s criminal law through the enactment of the National Criminal Code (Law Number 1 of 2023) signifies a fundamental transformation in the orientation of sentencing objectives. This shift reflects a transition from a retributive approach, which primarily emphasizes punishment of offenders, toward a more humanistic and restorative justice–oriented paradigm. This article aims to critically examine the reorientation of sentencing purposes within the National Criminal Code and its implications for the criminal justice system in Indonesia. This study employs a normative juridical method, utilizing both statutory and conceptual approaches, by analyzing relevant legal regulations and scholarly literature. The findings reveal that the objectives of sentencing under the National Criminal Code are no longer confined to the imposition of penalties, but also encompass crime prevention, offender rehabilitation, victim restoration, and social reintegration. This humanistic approach positions individuals as the central focus of criminal law, striving to balance the interests of offenders, victims, and society. Therefore, this reform is expected to foster a more equitable, responsive, and humane criminal justice system.